A Study of Patients with Acute Superficial Abscesses at Kosti Teaching Hospital - . Rahim, Somia K A; Kh Saeed, Osman; Mirghani, Omer A. (Gezira Journal of Health Sciences, 2016)
Abstract: Background: Acute superficial abscesses are among the most common clinical conditions requiring surgical treatment at the Accident and Emergency Department of Kosti Teaching Hospital. Unfortunately, epidemiological, clinical and bacteriological information on both patients and causative micro-organism are lacking or non-existent of patients with acute superficial abscess in White Nile State –Sudan. In this era of evidence based medicine, obtaining such information helps in making guidelines for treatment and prevention of this common surgical problem. Objectives: To determine epidemiological characteristics, risk factors and causative organism and its antibiotic susceptibility of the acute superficial abscesses in Kosti Teaching Hospital. Patients and Methods: a prospective observational descriptive study, involving a convenience sample of patients who presented to Kosti teaching hospital emergency department with acute superficial abscesses in the period from May 2012 to July2012.  . A pro-forma was used to collect personal, clinical, operative and bacteriological data of these patients . The incision and drainage of the abscesses were performed as a day case. Swabs of pus were sent to laboratory for culture and sensitivity tests. Results: A total of 62 patients were included in the study. There were 40(64.5%) males  and 22(35.5%) were females. 82.3% of the patientswere below 40 years. Forty three (69.3%) of the patients had no predisposing cause, trauma obtained in17 (27.4%) patients, 4 (6. 4%) patients were diabetics and 2(3.2%) patients had history of intramuscular injection The most common site of the abscess was the upper limbs (45.2%), followed by lower limbs (24.2%). Staphylococcus aureus was isolated from most of the patients (82.2%). Conclusion: Acute superficial abscesses mainly affect the extremities of the young who have no known predisposing factors. The main causative organism of these abscesses was the staphylococcus aureus. A relatively cheap antibiotic like ciprofloxacin and gentamicin can be used for treatment of acute superficial abscesses. Guidelines for incisions and drainage and antibiotic treatment of abscesses must be established.